2021
DOI: 10.1038/s41598-021-98177-4
|View full text |Cite
|
Sign up to set email alerts
|

High levels of osteoprotegerin are associated with coronary artery calcification in patients suspected of a chronic coronary syndrome

Abstract: Plasma osteoprotegerin (OPG) and vascular smooth muscle cell (VSMC) derived extracellular vesicles (EVs) are important regulators in the process of vascular calcification (VC). In population studies, high levels of OPG are associated with events. In animal studies, however, high OPG levels result in reduction of VC. VSMC-derived EVs are assumed to be responsible for OPG transport and VC but this role has not been studied. For this, we investigated the association between OPG in plasma and circulating EVs with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 57 publications
2
6
0
Order By: Relevance
“…Patients with CS have also increased concentrations of osteoprotegerin (29), a glycoprotein associated with coronary artery calcification (30). Whether low fetuin A in the course of CS, as observed in our study, contributes to increased coronary artery calcification and consequently cardiovascular mortality remains to be clarified.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Patients with CS have also increased concentrations of osteoprotegerin (29), a glycoprotein associated with coronary artery calcification (30). Whether low fetuin A in the course of CS, as observed in our study, contributes to increased coronary artery calcification and consequently cardiovascular mortality remains to be clarified.…”
Section: Discussionsupporting
confidence: 56%
“…Increased Agatson score, a measure of coronary calcification, was observed in subjects with active CS or a history of CS ( 26 ), as well as a relation between increased cortisol reactivity to stress and greater extent of coronary artery calcification in short-time and prolonged observation – in healthy subjects ( 27 , 28 ). Patients with CS have also increased concentrations of osteoprotegerin ( 29 ), a glycoprotein associated with coronary artery calcification ( 30 ). Whether low fetuin A in the course of CS, as observed in our study, contributes to increased coronary artery calcification and consequently cardiovascular mortality remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 38 studies are published that investigated a possible association between OPG and arterial calcification ( Barbarash et al, 2016 ; Chai et al, 2017 ; Davaine et al, 2016 ; Diederichsen et al, 2017 ; Golovkin et al, 2016 ; Liu et al, 2019 ; Torii et al, 2016 ; Bernandes et al, 2019 ; Abedin et al, 2007 ; Asanuma et al, 2007 ; Bakhireva et al, 2008 ; Berezin and Kremzer, 2013a ; Bezerra et al, 2005 ; Dekker et al, 2021 ; Esteghamati et al, 2014 ; Frost et al, 2008 ; Golledge et al, 2008 ; Hosbond et al, 2014a ; Ketlogetswe et al, 2015 ; Kiani et al, 2017 ; Lieb et al, 2010 ; Liu et al, 2020 ; Mohammadpour et al, 2012 ; Nugroho and Widorini, 2017 ; Omland et al, 2007 ; Park et al, 2006 ; Pérez de Ciriza et al, 2014 ; Poornima et al, 2014 ; Poornima et al, 2018 ; Quercioli et al, 2012 ; Vinholt et al, 2013 ; Hosbond et al, 2014b ; Hwang et al, 2012 ; Kwon et al, 2016 ; Pesaro et al, 2018 ; Salari et al, 2017 ; Stȩpień et al, 2012 ; Wilund et al, 2008 ). Nineteen studies indicated a positive association ( Barbarash et al, 2016 ; Chai et al, 2017 ; Liu et al, 2019 ; Torii et al, 2016 ; Abedin et al, 2007 ; Asanuma et al, 2007 ; Dekker et al, 2021 ; Esteghamati et al, 2014 ; Golledge et al, 2008 ; Ketlogetswe et al, 2015 ; Liu et al, 2020 ; Nugroho and Widorini, 2017 ; Oml...…”
Section: Resultsmentioning
confidence: 99%
“…For example, we ascribed the better lipid profile and the non-significant difference in osteoprotegerin levels between groups, to the high prescription rate of statins in our atherosclerotic patients. 19 Osteoprotegerin is a vascular calcification inhibitor, 33 whose concentration is suppressed by statins. 17,18 The extensive use of statins may also explain the lack of relationship between osteoprotegerin and arterial stiffness in our CAS cohort.…”
Section: Discussionmentioning
confidence: 99%